Small Group Discussion (SGD) Through Whatsapp Group In Teaching English For Nursing Students - Nashir, Muhammad; Laili, Roudlotun Nurul (FKIP Universitas Islam Jember, 2020)
It cannot be denied that teaching English as a foreign language is very challenging because there are still many problems faces. Various responses can be found at class such as students’ attitude toward learning, learning outcomes, and students’ active involvement in carrying out group activities especially if it is categorized as a large class which consists of more than 30 students. Small group discussion (SGD) offers a solution in order to make students more active by interacting, exchanging information, maintaining opinion, and solving problems in a group. Meanwhile in 21st century era technological advances like social networks grow rapidly. Lately many students have accessed social media to find information and learning resources. One of social media which is popular among students and educators is WhatsApp. We can create WhatsApp group to share information and discuss the material, so it can optimize the smart phone function in education. This study aimed to observe the effectiveness of small group discussion incorporating with WhatsApp group in teaching English. The research design used was quasi experimental. Experimental class was treated by using small group discussion through WhatsApp group, while control class was taught through lecturing. The finding showed that the significance of t-count was 0.000. It was lower than 0.05. It revealed that there is significant effect on the use of small group discussion through WhatsApp group in teaching English as a foreign language. Through WhatsApp group students feel free to discuss everything, more confident and brave to express their ideas. So WhatsApp is effective to be implemented in learning process.